Effect of orange fibre on nutrient digestibility and fermentation products in faeces of cats fed kibble diets - Eugênio, Débora Alberici [UNESP]; Volpe, Lara Mantovani [UNESP]; Ribeiro, Priscila Martins [UNESP]; Baller, Mayara Aline [UNESP]; Pacheco, Letícia Graziele [UNESP]; Takahashi, Amanda Vitta [UNESP]; Pacheco, Peterson Dante Gavasso [UNESP]; Putarov, Thaila Cristina [UNESP]; Theodoro, Stephanie de Souza [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (Taylor & Francis, 2022)
The aim of the present study was to compare orange fibre, beet pulp and inulin as fibre sources for cats. A control diet (CON) was formulated without inclusion of a fibre source. Further experimental diets were also based on diet CON but were supplemented with 1% orange fibre (diet 1%OF); 3% orange fibre (diet 3%OF); 3% beet pulp (diet 3%BP) or 1% inulin (diet 1%IN). Forty cats were used in a randomised block design (4 blocks of 10 cats, 2 animals per food in each block, totalling 8 animals per treatment). Each block lasted 20 d, with 10 d of adaptation, 10 d of faecal collection for digestibility as well as evaluation of pH-value and fermentation products. The digestibility of dry matter, organic matter, crude protein, ether extract, starch and gross energy did not vary between diets. In diet 1%OF, dietary fibre revealed a greater digestibility than in diet CON (p < 0.05). Faecal production was higher in cats fed diets 3%OF and 3%BP than in those fed diet 1%IN (p < 0.05). Faecal concentrations of acetate and total short-chain fatty acids were higher for cats fed diet 3%BP than for those fed diets 1%IN and CON (p < 0.05), while diets 1%OF and 3%OF showed intermediate results. Faecal propionate concentration was higher for cats fed diet 3%BP, intermediate for diets 1%OF, 3%OF and 1%IN and lower for animals fed diet CON (p < 0.05). Compared with diets CON and 1%IN, the faecal concentration of tyramine was higher for cats fed diet 3%OF (p < 0.05). Orange fibre was fermentable; up to 3% inclusion it did not interfere with the digestibility of nutrients, faecal score and faecal moisture content, and promoted the formation of short-chain fatty acids and tyramine by the intestinal microbiota, with possible effects on intestinal function.
Keywords: Beet pulp; byproducts; cats; digestibility; inulin; oranges; soluble fibre; tyramine